FUKOSANTIN: KAROTENOID BERHARGA DARI MAKROALGA COKLAT - Tri Handayani (Pusat Penelitian Oseanografi LIPI, 2018)
FUCOXANTHIN: A HIGH VALUE CAROTENOID FROM BROWN MACROALGAE. Fucoxanthin is carotenoid that can be found in marine brown seaweed (macroalgae) and diatoms (microalgae). Fucoxanthin has been isolated from brown macroalgae for its bioactivities study, including: Cystoceira barbata, Sargassum aquifolium, Sargassum filipendula, Sargassum ilicifolium, Sargassum wightii, Alaria crassifolia, Cladosiphon okamuranus, Cystoseira hakodatensis, Eisenia bicyclis, Fucus serratus, Fucus vesiculosus, Hijikia fusiformis, Ishige okamurae, Kjellmaniella crassifolia, Laminaria japonica, Laminaria ochotensis, Myagropsis myagroides, Padina tetrastromatica, Petalonia binghamiae, Sargassum fulvellum, Sargassum heterophyllum, Sargassum horneri, Sargassum siliquastrum, Undaria pinnatifida, Sargassum longifolium, Padina sp, Turbinaria sp, and Undaria pinnatifida. The amount of fucoxanthin depends on the species of algae. Fucoxanthin has been reported to have bioactivities, i.e. antioxidant, antiinflammatory, anticancer, antiobese, antidiabetic, antiangiogenic, and pigmentation inhibitory.